THE INFLUENCE OF PUBLIC POLICY AND COOKING OIL PRICES ON COOKING OIL SUPPLIES IN SARIJADI VILLAGE - Saptono Kusdanu Waskito; Muji Rahayu (SEAN Institute, 2022)
This study aims to determine and analyze the effect of public policy and cooking oil prices on the supply of cooking oil in Sarijadi Village. The number of samples filling the questionnaire was 97 people. Multiple Linear Regression Equation. Y = 8.052 +0.578 X1 + 0.575 X2. This means that without Public Policy and Cooking Oil Prices. The value of the Cooking Oil Inventory is only 8.052. If the Public Policy and Cooking Oil Price are added, and the addition is done simultaneously, the Cooking Oil Inventory which was originally valued at 8.052 will increase to 8.052 + 0.578 +0.575 or 9.025. The author proves that there is a positive and significant effect Public Policy on Cooking Oil Inventory with t value 6.943 > t table 0.67. The significance value is 0.000 < 0.05. The author proves that there is a positive and significant effect of Cooking Oil Prices on Cooking Oil Inventories with a t value of 4.993 > t table 0.67. The significance value is 0.000 < 0.05. The author proves that there is a positive and significant effect of Public Policy and Cooking Oil Prices simultaneously on Cooking Oil Inventories with F count 245.796 > F table 3.94. The significance value is 0.000 < 0.05. The government should anticipate the behavior of cooking oil entrepreneurs, cooking oil packers, retailers, sellers in people's markets, supermarkets, the community so that supplies can be controlled.